Globalization, Cultural Diversity, Education - Vez López, Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2018)
With the advent of globalization and an ever-growing widespread access to information and communication technologies (ICTs), the cultural minorities become increasingly involved in a process of cultural standardization at the expense of their own cultural identity and language. Different social, economic, and technological elements, together with mainstream education play a very important role in the negation of regional and local cultural identities. These factors lead minoritarian cultural groups to see the dominant culture as more attractive and modern, which often pushes them to abandon their own culture in the hope of better employment perspectives and a better lifestyle for them and their children. In the face of this cultural crisis, intercultural education for all can help stop the erosion of cultural diversity around the world.